摆动导杆机构键合图建模新方法 - 何雅槐; 唐进元; 陈海锋 (Jixie chuandong)
The bond graph modeling of swing guide-bar mechanism is researched.An integrated modeling method based on the combination of virtual work principle and bond graph is put forward.Firstly,the centroid movement rule of each bar and the bond graph model of the turning or moving pair are researched by the principle of virtual work and the geometry relation between each bar.Then the bond graph modeling of the system is established by making up the bond graph models of each bar.The correctness of this method is verified by simulation calculation.As a consequence,modeling process is simplified using this method,and the difficulty on bond graph modeling for complex planer linkage is released.Thus a considerable referential value has to be notified for bond graph modeling in the area of mechanism.